2007
DOI: 10.1126/science.1142179
|View full text |Cite
|
Sign up to set email alerts
|

Brain IRS2 Signaling Coordinates Life Span and Nutrient Homeostasis

Abstract: Reduced insulin-like signaling extends the life span of Caenorhabditis elegans and Drosophila . Here, we show that, in mice, less insulin receptor substrate–2 (Irs2) signaling throughout the body or just in the brain extended life span up to 18%. At 22 months of age, brain-specific Irs2 knockout mice were overweight, hyperinsulinemic, and glucose intolerant; however, compared with control mice, they were more active and displayed greater g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
431
2
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 484 publications
(460 citation statements)
references
References 24 publications
(12 reference statements)
17
431
2
5
Order By: Relevance
“…Mutation of genes in this signaling pathway confers greater resistance to oxidative stress and phenotypic characteristics consistent with delayed and slowed aging. In particular, heterozygous deletion of the IGF1R gene has been shown to causes a modest reduction in size, improves stress resistance and extends life span in mice (Hoizenberger 2003 Table 4 Allele combination effect on longevity life span and extend the life span of mice up to 20% (Taguchi et al 2007). In humans, IGF1R variants have been found associated with susceptibility to metabolic syndrome-related phenotypes, in particular with the risk of having insulin resistance and arterial hypertension (Sookoian et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of genes in this signaling pathway confers greater resistance to oxidative stress and phenotypic characteristics consistent with delayed and slowed aging. In particular, heterozygous deletion of the IGF1R gene has been shown to causes a modest reduction in size, improves stress resistance and extends life span in mice (Hoizenberger 2003 Table 4 Allele combination effect on longevity life span and extend the life span of mice up to 20% (Taguchi et al 2007). In humans, IGF1R variants have been found associated with susceptibility to metabolic syndrome-related phenotypes, in particular with the risk of having insulin resistance and arterial hypertension (Sookoian et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A number of "aging genes" have been identified for which mutations significantly increase mouse lifespan and delay the onset of age-related disease (Prop1, Pit1, Ghr,Ghrhr,Irs1,Irs2,PappA,Clk1,Shc1,Igf1r,Kl,Adcy5,Surf1,Insr,Ucp2,Gpx4) (Brown-Borg et al, 1996;Kopchick and Laron, 1999;Migliaccio et al, 1999;Flurkey et al, 2001;Bluher et al, 2003;Holzenberger et al, 2003;Kurosu et al, 2005;Liu et al, 2005;Conti et al, 2006;Conover and Bale, 2007;Dell'Agnello et al, 2007;Ran et al, 2007;Taguchi et al, 2007;Yan et al, 2007;Selman et al, 2008). The extent to which these genes interact with CR-regulated pathways is unclear (Miller et al, 2002;Tsuchiya et al, 2004;Bonkowski et al, 2006;Swindell, 2007).…”
Section: Other "Aging Genes" Lack Unique Network Propertiesmentioning
confidence: 99%
“…For example, IIS regulates adult life span in both Caenorhabditis elegans, e.g., (Dorman et al 1995;Lin et al 1997) and Drosophila melanogastor, e.g., (Clancy et al 2001;Tatar et al 2001;Alic et al 2011). IIS also plays a key role in mammalian aging, with global (Holzenberger et al 2003;Selman et alKappeler et al 2008;Taguchi et al 2007) deletion of IIS genes extending lifespan in mice. In addition, this lifespan extension has been shown to be associated, in some models , with a greater period of adult life free from disease (see .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, currently only one study has reported antioxidant levels in long-lived IIS mutants, and this was limited to a single antioxidant enzyme in a single tissue. Taguchi et al (2007) reported that long-lived brain-specific insulin receptor substrate 2 heterozygous (bIrs2 +/− ) and homozygous (bIrs2 −/− ) knockout mice were protected against an age-associated decrease in postprandial manganese superoxide dismutase (MnSOD) levels. However, in contrast, a large amount of data on antioxidant enzyme status and oxidative damage has been reported for long-lived GH-deficient dwarf mice.…”
Section: Introductionmentioning
confidence: 99%